199 Baricitinib in patients with systemic lupus erythematosus: results from a phase 2, randomized, double-blind, placebo-controlled study. (April 2019) - Silk, Maria E; Wallace, Daniel J; Furie, Richard A; Tanaka, Yoshiya; Kalunian, Kenneth C; Mosca, Marta; Petri, Michelle; Dörner, Thomas; Cardiel, Mario H; Bruce, Ian N; Gomez, Elisa; DeLozier, Amy M; et al.
Abstract : Background: Baricitinib (Bari), an oral selective inhibitor of Janus kinase (JAK)1 and JAK2, has been approved for the treatment of rheumatoid arthritis (RA) in over 50 countries including the United States, European countries, and Japan. The purpose of this study was to report results from a 24 week global, Phase 2, double-blind, placebo (PBO)-controlled study of Bari in patients with systemic lupus erythematosus (SLE) receiving standard therapy. Methods: Patients with SLE (positive antinuclear antibody [ANA] or anti-double stranded DNA [anti-dsDNA], clinical SLE Disease Activity Index 2000 [SLEDAI-2K] 4, arthritis or rash required) receiving stable background SLE therapy were randomized 1:1:1 to PBO or Bari (2- or 4 mg) once-daily. The primary endpoint was resolution of arthritis or rash as defined by the SLEDAI-2K at Week 24. Results: Of 314 patients randomized, 79%, 82%, and 83% completed 24 weeks of treatment in the PBO, Bari 2 mg, and Bari 4 mg groups, respectively. At Week 24, a significantly greater proportion of patients in the Bari 4 mg group compared to PBO achieved resolution of arthritis or rash (67% vs 53%, p<0.05) and SLE Responder Index (SRI)−4 response (64% vs 48%, p<0.05). At Week 24, the proportions of patients achieving flare reduction (Safety of Estrogens in Lupus Erythematosus National Assessment [SELENA]-SLEDAI Flare Index [SFI]), Lupus Low Disease Activity State (LLDAS), Physicians Global Assessment, and tender joint count change from baseline were also significantly improved for Bari 4 mg compared to PBO (Table). No statistically significant differences were observed between Bari 2 mg and PBO in any of the above endpoints. There were no significant changes in anti-dsDNA or complement in patients treated with Bari. Rates of adverse events leading to treatment discontinuation and serious adverse events (SAEs) were higher for both Bari dose groups compared to PBO. There were no deaths, malignancies, major adverse cardiovascular events, tuberculosis, or serious herpes zoster infections; 1 SAE of deep vein thrombosis was reported in a patient with risk factors (Bari 4 mg group). Conclusions: In patients with SLE receiving standard background therapy, once-daily oral Bari 4 mg was associated with significant clinical improvements compared to PBO and an acceptable benefit/risk profile. These findings support further study of Bari as a potential therapy for patients with SLE. Funding Source(s): This study was funded by Eli Lilly and Company.